Sovereign Catastrophe Risk Pools : World Bank Technical Contribution to the G20 - World Bank Group (World Bank, Washington, DC, 2017)
More than 1 billion people have lifted themselves out of poverty in the past 15 years, but climate and disaster risks threaten these achievements. Global asset losses from disasters are now reaching an average of more than US$300 billion a year. A recent World Bank report finds that the impacts of disasters on well-being are equivalent to a US$520 billion drop in consumption (60 percent more than the asset losses usually reported) and force some 26 million people into poverty every year (Hallegatte et al., 2017). Moreover, countries face increasingly complex threats that often compound the negative impacts of disaster and climate shocks, ranging from migration caused by fragility and conflict situations, to the risk of pandemics. For instance, it is estimated that 93 percent of people facing extreme poverty today are living in countries that are politically fragile or environmentally vulnerable, and in many cases, both. The United Nations’ humanitarian appeal for 2017, for example, stands at a record US$22.2 billion, to help almost 93 million people affected by conflicts and natural disasters. Climate change exacerbates some of these risks by increasing the frequency and intensity of extreme weather events. In addition, economic growth and rapid urbanization increase exposure. Building resilience is therefore crucial to safeguard poverty reduction efforts and promote sustainable and inclusive development, particularly for the poor and vulnerable, who are the least able to cope with and adapt to increasing risks. To achieve the overarching objective of reducing the protection gap in vulnerable developing countries, and to catalyze action around these priority areas and activities, the G20 could promote the creation of a Global Partnership for Climate and Disaster Risk Finance and Insurance Solutions. The Global Partnership could bring together relevant partners from developing and developed countries, international organizations, the private sector, and civil society. To achieve maximum impact, the Global Partnership would leverage the comparative advantages of all partners and build on the work of existing platforms and initiatives. It will leverage the technical expertise and capacity of the private insurance and reinsurance industry. The G20 could develop a work program structured around the four priority action areas identified above to specify how countries will support specific activities. Such efforts will not only promote financial protection and help close the protection gap, but will also support the broader disaster and climate resilience agenda.